Multi-organ distribution of phosphorylated α-synuclein histopathology in subjects with Lewy body disorders - Beach, Thomas G.; Adler, Charles H.; Sue, Lucia I.; Vedders, Linda; Lue, LihFen; White III, Charles L.; Akiyama, Haru; Caviness, John N.; Shill, Holly A.; Sabbagh, Marwan N.; Walker, Douglas G. (Acta neuropathologica, 2010)
A sensitive immunohistochemical method for phosphorylated α-synuclein was used to stain sets of sections of spinal cord and tissue from 41 different sites in the bodies of 92 subjects, including 23 normal elderly, 7 with incidental Lewy body disease (ILBD), 17 with Parkinson’s disease (PD), 9 with dementia with Lewy bodies (DLB), 19 with Alzheimer’s disease with Lewy bodies (ADLB) and 17 with Alzheimer’s disease with no Lewy bodies (ADNLB). The relative densities and frequencies of occurrence of phosphorylated α-synuclein histopathology (PASH) were tabulated and correlated with diagnostic category. The greatest densities and frequencies of PASH occurred in the spinal cord, followed by the paraspinal sympathetic ganglia, the vagus nerve, the gastrointestinal tract and endocrine organs. The frequency of PASH within other organs and tissue types was much lower. Spinal cord and peripheral PASH was most common in subjects with PD and DLB, where it appears likely that it is universally widespread. Subjects with ILBD had lesser densities of PASH within all regions, but had frequent involvement of the spinal cord and paraspinal sympathetic ganglia, with less-frequent involvement of end-organs. Subjects with ADLB had infrequent involvement of the spinal cord and paraspinal sympathetic ganglia with rare involvement of end-organs. Within the gastrointestinal tract, there was a rostrocaudal gradient of decreasing PASH frequency and density, with the lower esophagus and submandibular gland having the greatest involvement and the colon and rectum the lowest.